2012
DOI: 10.1098/rstb.2012.0243
|View full text |Cite
|
Sign up to set email alerts
|

Warming shifts top-down and bottom-up control of pond food web structure and function

Abstract: The effects of global and local environmental changes are transmitted through networks of interacting organisms to shape the structure of communities and the dynamics of ecosystems. We tested the impact of elevated temperature on the top-down and bottom-up forces structuring experimental freshwater pond food webs in western Canada over 16 months. Experimental warming was crossed with treatments manipulating the presence of planktivorous fish and eutrophication through enhanced nutrient supply. We found that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
241
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(281 citation statements)
references
References 64 publications
21
241
5
2
Order By: Relevance
“…Our results provide no support for this prediction as responses of viral and bacterial composition to the experimental treatments differed qualitatively (for example, response to nutrient addition in bacteria but not in viruses) and Mantel tests provided no evidence for overall compositional associations. Similarly, Shurin et al (2012) found that the response of viruses to experimental treatments of warming, fish predators and eutrophication was distinct from those of bacteria. Weak associations between bacteria and viruses can be expected if a large fraction of the viruses infect other organisms, such as phytoplankton cells.…”
Section: Discussionmentioning
confidence: 95%
“…Our results provide no support for this prediction as responses of viral and bacterial composition to the experimental treatments differed qualitatively (for example, response to nutrient addition in bacteria but not in viruses) and Mantel tests provided no evidence for overall compositional associations. Similarly, Shurin et al (2012) found that the response of viruses to experimental treatments of warming, fish predators and eutrophication was distinct from those of bacteria. Weak associations between bacteria and viruses can be expected if a large fraction of the viruses infect other organisms, such as phytoplankton cells.…”
Section: Discussionmentioning
confidence: 95%
“…An increasing strength of plantherbivore interactions has been found to coincide with rising temperatures (Barton et al, 2009;O'Connor, 2009;Shurin et al, 2012). Compared to the amount of studies currently investigating the effects of global warming on trophic interactions, there seems to be only relatively few studies investigating the role of omnivores in this situation (e.g., Boersma et al (2016)).…”
Section: Discussionmentioning
confidence: 99%
“…alterations of trophic interactions (O'Connor, 2009), which may have cascading effects throughout the food web (Shurin et al, 2012) due to a mismatch in timing (Winder and Schindler, 2004) or change in food quality. Plant nutrient concentrations and the C:nutrient stoichiometry have been shown to be strong predictors of plant consumption rates across ecosystems (Elser et al, 2000a;Sterner and Elser, 2002).…”
Section: Introductionmentioning
confidence: 99%